2019
DOI: 10.1097/md.0000000000014287
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most prevalent cancers worldwide. However, the precise mechanisms of the development and progression of HCC remain unclear. The present study attempted to identify and functionally analyze the differentially expressed genes between HCC and cirrhotic tissues by using comprehensive bioinformatics analyses. Methods: The GSE63898 gene expression profile was downloaded from the Gene Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
5
25
0
Order By: Relevance
“…CCNB1, a regulatory protein that plays an essential role in controlling mitosis, was upregulated in HCC patients with poor outcome [62,63]. Liu et al reported that CCNB1 was closely correlated with GTSE1: after GTSE1 knockdown, CCNB1 and FoxM1 were significantly downregulated, while p53 expression was significantly increased in BCa.…”
Section: The Hub Genes Potentially Associated With the Clinical Prognmentioning
confidence: 99%
“…CCNB1, a regulatory protein that plays an essential role in controlling mitosis, was upregulated in HCC patients with poor outcome [62,63]. Liu et al reported that CCNB1 was closely correlated with GTSE1: after GTSE1 knockdown, CCNB1 and FoxM1 were significantly downregulated, while p53 expression was significantly increased in BCa.…”
Section: The Hub Genes Potentially Associated With the Clinical Prognmentioning
confidence: 99%
“…In previous studies, bioinformatics analysis of microarray and RNA-seq gene data profiles identified key onco-genes, such as cell division cycle 20 and cell division cycle associated 5 involved in the prognosis of HCC (7,8). In a preliminary bioinformatics study, Wu et al (9) identified 12 genes, including non-SMC condensin I complex subunit G and TTK protein kinase that were associated with the progression of HCC. In addition, Pan et al (10) revealed that micro(mi) RNA-15b-5p serves an oncogenic role in HCC.…”
Section: Identification Of 40s Ribosomal Protein S8 As a Novel Biomarmentioning
confidence: 99%
“…In the past, studies focusing on analysis of HCC-related genes usually included patients with HCC caused by various factors such as chronic hepatitis B or C virus infection and alcoholic liver disease [18,19,34]. But there is limited research that only discusses HCV-related liver cancer on the background of HCV-cirrhosis, so we re-analyzed the data in GSE6764.…”
Section: Disscusionmentioning
confidence: 99%
“…Now, there are rich public repositories of RNA-seq and microarray datasets, such as Gene Expression Omnibus (GEO) database [16] and The Cancer Genome Atlas (TCGA) [17]. Further analysis of those datasets combined with computational approach such as prediction model can provide the opportunity to establish a novel biomarker for disease diagnosis with high accuracy [18,19].…”
Section: Introductionmentioning
confidence: 99%